Factors influencing the implementation of customer relationship management (CRM) strategy in the hotel industry: consumers’ perspective - MD. Ashraful Azam, khan; Rahman, Muhammad Sabbir (The International Journal Research Publication's, 2014)

(untitled)
The paper aims to empirically test the relationship of customers' privacy, business ethics, service efficiency and corporate social responsibility (CSR) towards the implementation of customer relationship management (CRM). A survey method, technique was used in this study with 260 respondents from different tourist destinations in Malaysia. To test the hypotheses, this research applied multiple regression technique. Business ethics were found to have the most important influence on the implementation of CRM in hotel industry followed by privacy, service efficiency and CSR. This research agreed that managers in hotel industries should tailor the implementation of a CRM strategy by concerning more on the practice of business ethics in their service performance.